(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article analyzes the importance of grain seed production and its impact on productivity. High-quality and efficient organization of seed production is considered a key factor in increasing grain yields. The article considers the pre-sowing preparation of seeds, selection of quality seeds, seed storage conditions, seed sowing technology, and the impact of seed production measures on productivity. Also, based on modern agronomic approaches and research results, the role of seed production in obtaining high yields and its contribution to sustainable development in agriculture are highlighted.